التأمين الصحي في ماليزيا وليبيا - Musbah Ramadan Elsheltat
This study aims to clarify on the realities of health insurance products which are practiced in Takaful Ikhlas Malaysia and Insurance Libya Company. Theoretically, this thesis aims to discuss the general concepts of insurance before discussing the concepts of health insurance in depth, and the various problems related to it. For examples, the hukm, its importance, characteristics and its relation with other insurance. This study discusses rulings related to health insurance from the syariah perspective by referring to and examine the views of fiqh scholars. From the practical side, this study will discuss on the implementation of health insurance as practiced in the Middle East which is represented by Insurance Libya Company and in South East Asia which is represented by Takaful Ikhlas Malaysia; this is by providing briefly on the historical development of insurance market in both countries, also by introducing the two companies which market the products of health insurance. Besides examining the types of contract which is used between the company and the customer, this study aims to discuss the suitability of the standard outline by the syariah which is used by the majority of takaful companies. This study finds that generally, insurance is legally permissibile in Shariah. However, there are disputes regarding the implementation of the system. One of the characteristics of health insurance is to provide health services to all walks of life. This study finds that the health insurance as applied in Insurance Libya Company which is based on contract of exchange is against the Syariah. However, the concept of health insurance in Takaful Ikhlas, which is based on agency and gift is allowed to be practiced as there is compatibility with the standards outlines by the syariah and at the international level and it complies with the maqasid syariah.